POTANTIAL OF BIOAGENTS FOR SUSTAINABLE MANAGEMENT OF SCLEROTIUM ROT OF FRENCH BEAN (Journal of Plant Disease Sciences, 2026)
Sclerotium rot, caused by Sclerotium rolfsii, is a destructive soil-borne disease that severely limits French bean productivity, highlighting the need for ecologically safe and sustainable disease management strategies. The present study evaluated the efficacy of five bioagents—Trichoderma harzianum, Trichoderma asperellum, Bacillus subtilis, Pseudomonas fluorescens, and a microbial consortium (Biomix)—under pot culture conditions using the sick soil technique. Captan 50% WP served as the chemical standard check. All bioagent treatments significantly improved seed germination (51.67–83.33%) compared with the untreated control (41.67%). Trichoderma harzianum recorded the highest seed germination (83.33%), followed by Bacillus subtilis, while Captan 50% WP achieved 61.67% germination. Pre-emergence seed rot (PRESR) was significantly reduced in all treatments (16.67–48.33%) compared with the control (58.33%), with T. harzianum showing the lowest incidence (16.67%), followed by B. subtilis (25.00%). Captan recorded 38.33% PRESR. Similarly, post-emergence seedling mortality (POESM) ranged from 13.33% to 33.33% among the bioagent treatments, compared with 40.00% in the untreated control. T. harzianum again proved most effective with the lowest POESM (13.33%), followed by B. subtilis (18.33%), whereas Captan recorded 28.33%. Overall mean mortality was lowest with T. harzianum (15.00%), while Captan (33.33%) performed better than T. asperellum and Biomix. The results demonstrate that T. harzianum and B. subtilis are highly effective, eco-friendly bioagents for suppressing Sclerotium rot and represent promising sustainable alternatives to chemical fungicides for the management of the disease in French bean cultivation.
Keywords: Bioagents; French bean; Sclerotium; Seed germination